VIDEOCONFERENCING ON EDUCATION: A CASE STUDY WITH TEACHERS OF BASIC EDUCATION - Paulo Sérgio Garcia; Vilmar Malacarne; Luiz Caldeira Brant de Tolentino Neto (Editora da Universidade de Santa Cruz do Sul, 2013)
This study investigated teachers' objectives for using videoconferencing (VC), their forms of use, and advantages and difficulties faced in the context of public schools. It was also analyzed VC contribution to teacher education and the skills that teachers require to use it. It was used interviews with 17 teachers who participated in projects. The data analyzed qualitatively revealed that teachers had objectives related to the expansion of the content, the study of other cultures, the creation of new teaching methods and techniques, the encouragement of the students in decision-making, and the motivation of the students. Forms of use were associated with lectures and talks delivered by experts. Among the main difficulties were the lack of support and time for teacher planning his activities, and lack of technical support. The VC can contribute with teacher education in updating teacher knowledge, and in the process of learning how to use new technologies. Among the competencies required are: master the use of technologies, control physical space, and master the strategies of dynamics of the use. The results promote further discussions on teaching practices and classroom management, both in pre-service and in-service education.